The Social Tasks of Friendship: Do Boys and Girls Excel in Different Tasks?. (14th November 2016) - Rose, Amanda J.; Asher, Steven R.
Abstract: Research documents the strengths of girls' friendships compared to boys' friendships leading to the inference that boys are not very skilled as friends. In this article, we use a friendship tasks framework to propose that this inference is premature and should be reconciled with evidence that boys are as satisfied as girls with their friendships and that their friendships are as stable over time. We also propose that the inference arises partly because the friendship tasks that girls handle well have been studied extensively, whereas certain friendship tasks boys handle as well as or more successfully than girls are understudied. These tasks include being a fun and enjoyable companion, coping when a friend violates a core expectation of friendship, and sustaining friendships in the broader social context of a friend having other friends. Finally, we suggest that girls and boys who develop skills to respond to a range of friendship tasks will benefit in the long term.